2013
DOI: 10.4103/2231-0746.110069
|View full text |Cite
|
Sign up to set email alerts
|

TMJ imaging by CBCT: Current scenario

Abstract: Radiographic examination forms an integral component of the clinical assessment routine in patients with temporomandibular joint disorders (TMJ). There are several imaging modalities to visualize the TMJ. Cone beam computed tomography (CBCT) is a developing technique that is being increasingly used in dentomaxillofacial imaging due to its relatively low-dose high-spatial-resolution characteristics. Research in TMJ imaging has been greatly inspired by the advent of CBCT. In this paper we aim to discuss the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 18 publications
1
39
0
3
Order By: Relevance
“…4 Available literature on CBCT has become extensive since then, including reviews for application to the TMJ. [5][6][7][8] The present overview will give an update on TMJ imaging using CBCT and its diagnostic value compared with other imaging modalities, with main sections on diagnostic accuracy and OA. The usefulness of CBCT in the diagnostic assessment of other TMJ conditions will be shortly reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…4 Available literature on CBCT has become extensive since then, including reviews for application to the TMJ. [5][6][7][8] The present overview will give an update on TMJ imaging using CBCT and its diagnostic value compared with other imaging modalities, with main sections on diagnostic accuracy and OA. The usefulness of CBCT in the diagnostic assessment of other TMJ conditions will be shortly reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…An etiologic complex of factors such as trauma, emotional stress, muscular hyperactivity, and inflammatory and degenerative diseases may compromise the equilibrium of the temporomandibular joint (TMJ), leading to the development of temporomandibular disorder (TMD) 1 . The symptoms of TMD include decreased jaw mobility, pain in masticatory muscles, TMJ pain, joint sounds, and restriction or deviation in mouth opening 2 ; however, pain is the main symptom of TMD and also the major reason for patients to seek treatment 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Kretapirom et al 13) have indicated that magnetic resonance imaging (MRI) images of RA patients with TMJ involvement showed more frequent joint effusion and synovial proliferation than temporomandibular disorder (TMD) patients. In recent times, cone-beam CT (CBCT) has been used for assessment of TMJs because it is more economical and has a lower radiation exposure than conventional CT. 14) Other studies have proposed that CBCT images are superior to corrected angle linear tomography, panoramic projections 15) and MRI. 16) Despite the advantages of CBCT in diagnosing osseous change of TMJs, the study evaluating CBCT TMJ images of RA patients has not been performed yet.…”
Section: Introductionmentioning
confidence: 99%